An extended multi-attribute group decision approach for selection of outsourcing services activities for information technology under risks. (19th March 2019) - Mousavi, S. Meysam; Gitinavard, H.
In recent years, selection of outsourcing services activities for information technology (IT) which are defined under some outsourcing projects is a challenge for companies under competitive and uncertain environments. To address the issue, assessment techniques via group decision-making could be provided to appropriately appraise the candidates regarding the incomplete information and existing complexity. This study proposes a new integrated group assessment approach based on interval-valued hesitant fuzzy (IVHF) environment to select the best outsourcing projects regarding risks and incomplete information. The proposed approach is established via some procedures to determine experts' weights, criteria weights and candidates' rankings. The interval-valued hesitant fuzzy-collective wisdom weighting (IVHF-CWW) method is presented to compute the weight of each expert/decision maker (DM). Moreover, the interval-valued hesitant fuzzy-preference weighting (IVHF-PW) technique is presented to determine weights of evaluation criteria. Furthermore, the IVHF-utility index approach is elaborated to rank the candidate outsourcing projects. Finally, a practical study is provided to check the feasibility and validity of the proposed interval-valued hesitant fuzzy-integrated group decision-making (IVHF-IGDM) approach.